1981
DOI: 10.1080/00288233.1981.10420890
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the response of pasture legumes to phosphorus in a controlled environment

Abstract: White clover, red clover, suckling clover, and lotus were grown under a controlled environment in soil to which phosphorus had been added at levels of 50, 250, 600, and 2000 ppm w/w. Growth analysis was used to explain differences in yield in terms of attributes describing growth, P uptake, and assimilation. The yield of white clover, red clover, and lotus increased markedly with P supply. Suckling clover responded less to P and its yields were smaller than those of the other species except that of lotus at 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…The slight rise in P concentration of youngest mature leaves and the absence of a rise with P supply in total P concentration of sets of adjacent leaves is consistent with other observations indicating a relatively small increase in P concentration with increases in P supply in lotus (Davis 1981b, c;Hart et al 1981a).…”
Section: Discussionsupporting
confidence: 79%
“…The slight rise in P concentration of youngest mature leaves and the absence of a rise with P supply in total P concentration of sets of adjacent leaves is consistent with other observations indicating a relatively small increase in P concentration with increases in P supply in lotus (Davis 1981b, c;Hart et al 1981a).…”
Section: Discussionsupporting
confidence: 79%
“…There is potential to decrease P losses to surface runoff if plant species are chosen that avoid excessive P concentrations in foliage. Work of Hart et al (1981) indicates that among legumes grown at a similar soil test P concentration, white clover stores greater quantities of P in foliage. Further decreases in P losses, and savings in P fertiliser, could be achieved if this species reaches the near maximum yield at low soil test P concentrations.…”
Section: Management Considerationsmentioning
confidence: 98%
“…Shoot N concentrations of white clover gradually decrease with increasing levels of P supply (Caradus et al, 1993). Hart et al (1981) concluded that growth of white clover plants reliant on N from biological N2 fixation was limited by N at high levels of P supply. They found that root/shoot ratio of white clover remained constant after 80% maximum yield was reached.…”
Section: Effect Of Phosphorus Levelmentioning
confidence: 98%